The Contemporary Dance Economy Problems and Potentials in the Contemporary Neoliberal Moment - Paramana, Katerina (Edinburgh: Edinburgh University Press, 2017)
RESUMEN: Michel Foucault suggest that "conduct" is not only something we do, but something that is done to us, as well as a behavior or practice that is an effect of other forms of conduct. How is the conduct of the dance field - in the different ways that Foucault is referring to it - affected by, and affecting neoliberalism? What is dance's role in the contemporary neoliberal moment? These are the question I unpick in this article. I do so, first, by using Foucault's thinking on neoliberalism and the relationship between conduct, biopolitics, and neoliberal governmentality in order to illustrate how bodies of individuals and that of society are affected by the neoliberal economy. Wendy Brown's work on neoliberalism, which builds on Foucault's thinking, is interweaved in this discussion to allow me to address neoliberalism's function and effects in the contemporary moment. Second, I examine some of the problems of the contemporary dance economy as I, and other scholar-practitioners, have identified them, and address their relationship to neoliberalism, conduct, governmentality, and biopolitics - how they result from conducts suggested by neoliberalism or helping it do its work by becoming conducts of the field. I propose ways we might address them, suggesting that it is urgent that we do so if we are to advance the field and resist neoliberalism. For this, I use examples from conversations that recently took place in the field, such as at PAF London (2015), Sadler's Wells Summer University (2015), and Resilience: Articulating Dance Knowledges in the 21st Century and Post Dance conferences (2015). I argue that dance has an important role to play in changing today's world, but needs to come to terms with what I refer to as its "fears", assert itself, and take action. In many ways, this article constitutes a critique of the contemporary dance economy; a critique that, by showing the relation of our conduct to conducts imposed by larger economies, aspires at articulating our role as central to both advancing the field and effecting social change. PALABRAS CLAVE: Dance, contemporary, problems, potentials, conduct, neoliberalism, economy